Analisis Potensi Bahaya dalam Kegiatan Distribusi BBM di PT. XYZ Menggunakan Metode Hazard Identification Risk Assessement and Determining Control (HIRADC) - Prasetyo, Desnata Vanness; Syamtinningrum, Maeka Dita Puspa; Sarungu, Selvia (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
XYZ is a company operating in the downstream Oil and Gas (MIGAS) sector. Its business activities include marketing and distribution of energy products, one of which is the fuel distribution process. This research analyzes the potential dangers in fuel distribution activities at PT XYZ. The aim of this research is to find out the potential dangers that can occur in the process of fuel distribution activities, to find out the level of risk of danger that can occur in the process of fuel distribution activities, to find out how to control risks in the process of fuel distribution activities. Then the results of this research are that there are 19 potential dangers from 10 activities in the distribution process at PT XYZ. The level of risk of work accidents in fuel distribution activities has risk levels ranging from the Medium category to the High Risk category in each activity, can be categorized into seven (7) categories (Medium) and Twelve (12) categories (High Risk) as well as risk control that has been carried out to reduce the level of risk by using a control hierarchy, namely Engineering control with 11 controls, administration with 25 controls, and Use of Personal Protective Equipment (PPE) with 17 controls.